2018
DOI: 10.3389/fmicb.2018.01876
|View full text |Cite
|
Sign up to set email alerts
|

Association Between agr Type, Virulence Factors, Biofilm Formation and Antibiotic Resistance of Staphylococcus aureus Isolates From Pork Production

Abstract: Livestock-associated Staphylococcus aureus colonization and/or infections exist in pigs and people in frequent contact with pigs. In this study, a total of 130 S. aureus isolates obtained from different stages of pork production were subjected to antimicrobial susceptibility, biofilm formation, as well as PCR screening to identify virulence genes, and the accessory gene regulator alleles (agr). Among all 130 S. aureus isolates, 109 (83.8%, 109/130) isolates were positive for agr. All swine farms isolates belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
7
37
0
1
Order By: Relevance
“…Thus, the resistance of bacteria to antibiotics is inappropriate marker for its efficiency to biofilm formation. Obtained results were supported by recent study [34], which revealed that there was no significant difference among strong, moderate, and weak biofilm producers in their resistance to penicillin, cefoxitin, and chloramphenicol. However, Qi et al noticed that the correlation between the capacity of biofilm formation and the resistance of Acinetobacter baumannii isolates to antibiotics was negative, which mean that the biofilm forming isolates are less dependent on antibiotic resistance than no biofilm-forming isolates for survival [35].…”
Section: Discussionsupporting
confidence: 78%
“…Thus, the resistance of bacteria to antibiotics is inappropriate marker for its efficiency to biofilm formation. Obtained results were supported by recent study [34], which revealed that there was no significant difference among strong, moderate, and weak biofilm producers in their resistance to penicillin, cefoxitin, and chloramphenicol. However, Qi et al noticed that the correlation between the capacity of biofilm formation and the resistance of Acinetobacter baumannii isolates to antibiotics was negative, which mean that the biofilm forming isolates are less dependent on antibiotic resistance than no biofilm-forming isolates for survival [35].…”
Section: Discussionsupporting
confidence: 78%
“…The mechanisms beneath such resistance are diverse and lack antimicrobial diffusion into the biofilm matrix and the presence of recalcitrant cells, such as those belonging to the viable but not cultivable phenotype [ 82 ]. In S. aureus , the ability to form biofilms is directly related to the presence of virulence factors such as adhesins [ 83 ], and this structure contributes to the dissemination of resistance genes in the cells therein [ 5 ]. In this study, 65.52% of the resulting MRSA isolates were classified as biofilm-producing at 24 h. However, different levels of biofilm production were detected, in which most of the producers displayed low levels of biofilm production (i.e., weak producers, 44.83%) (see Section 3.4 .…”
Section: Discussionmentioning
confidence: 99%
“…In S. aureus, the accessory gene regulator (agr) and the staphylococcal accessory regulator (sarA) are genetic loci that determine the regulation and control of the expression of several virulence determinants [57]. Both sarA and agr play global regulatory roles in the limitation and/or propagation of S. aureus biofilm formation [20,60].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of biofilms is a complex process depending on several factors like nutrient availability, pH value, oxygen level, and surface properties [18]. In addition, biofilm formation in S. aureus is under the control of two genetic loci, sarA (staphylococcal accessory regulator) and agr (accessory gene regulator) quorum-sensing system [19,20].…”
Section: Introductionmentioning
confidence: 99%